Kim (World Classics, ,, 1990)
In a vividly drawn India of the late 19th century, orphan Kimball O'Hara is on the cusp of manhood. Living as a beggar, it isn't until Kim befriends an aged Tibetan Lama that his life transforms: the old man is on a quest to find the legendary River of the Arrow and achieve Enlightenment, and together they embark on an adventure through this impoverished, beautiful, chaotic nation in the grip of the Great Game, the conflict during which the British and Russian Empires raced to control Central Asia. But when Kim becomes a pawn in the Game, he must face the most difficult choice of all: his companion or his country?

The sword in the stone (Once and future king, 1, 1, 2008)
A retelling of the Arthurian legend.

Greek gods and heroes (Laurel-leaf library, ,, 1965)
A retelling of the greatest myths and legends of the ancient Greek gods and heroes for readers of all ages by a celebrated historical novelist. In the ancient past, the Gods and Goddesses of ancient Greece lived on Mount Olympus and ruled the world of mortals. Famous heroes shaped the course of history, beautiful women drew the gazes of gods and men alike, and the gods were both fickle in their favors and breathtakingly generous to those they smiled upon. From Midas' tragic gift to the exploits of Hercules and the curse of Pandora, renowned classicist and historical novelist Robert Graves brings the legends of ancient Greece to life in a lively, accessible way that's sure to appeal to everyone; from children to adults, and from casual readers to serious scholars.

Island of the blue dolphins (Island of the Blue Dolphins, ,, 1990)
Left alone on a beautiful but isolated island off the coast of California, a young Indian girl spends eighteen years, not only merely surviving through her enormous courage and self-reliance, but also finding a measure of happiness in her solitary life.

The black pearl (Laurel-leaf library, ,, 1996)
In Baja California, Mexico, sixteen-year-old Ramon is determined to claim the legendary black "Pearl of Heaven" lying at the bottom of the Vermilion Sea, but first he must outwit the notorious, and greatly feared, devil ray, Manta Diablo.

The pigman (Laurel-leaf library, ,, 2009)
A teenage boy and girl, high school sophomores from unhappy homes, tell of their bizarre relationship with an old man. Two lonely high school students befriend a strange old man, Mr. Pignati. An intensely moving story of believably alienated young people.

Are you there, God? It's me, Margaret (Laurel-leaf library, ,, 1990)
Faced with the difficulties of growing up and choosing a religion, a twelve-year-old girl talks over her problems with her own private God.

That was then, this is now (Laurel-leaf library, ,, 1998)
Sixteen-year-old Mark and Bryon have been like brothers since childhood, but now, as their involvement with girls, gangs, and drugs increases, their relationship seems to gradually disintegrate.

The chocolate war (Laurel-leaf library, ,, 1975)
A high school freshman discovers the devastating consequences of refusing to join in the school's annual fund raising drive and arousing the wrath of the school bullies.
Who is this Robert Cormier anyway? / by Patty Campbell , In his own words / Robert Cormier , Questions for discussion.

Frankenstein, or, The modern Prometheus (New York Public Library collector's edition, ,, 1990)
Resurrect this horror classic by Mary Shelley with this completely unabridged edition of Frankenstein. Mary Shelley's classic Frankenstein pioneered the deeply explored battle between monster and man. Follow three narratives in this ageless tale that navigates fear, fixation, love, and desire, while finding an anchor in humanity. The combination of fantastical elements and scientific exploration makes this Mary Shelley novel one of the first true models of science fiction. This new edition of Frankenstein stays true to the classic origins, but is provided with a whole new life by a beautifully designed, jacketed hardcover format. An introduction by writer and English professor Catherine Steindler, an author's introduction, and a timeline of the life and times of Mary Shelley completes this highly collectible edition.
Introduction , Chronology of Mary Shelley's life and work , Historical context of Frankenstein , Frankenstein , Interpretive notes , Critical excerpts , Questions for discussion , Suggestions for the Interested reader.

Never to forget: the Jews of the holocaust (Laurel-leaf library, ,, 1976)
Description Not Provided

Summer of fear (Laurel-leaf library, ,, 1976)
Soon after the arrival of cousin Julia, insidious occurrences begin that convince Rachel she is a witch and must be stopped before her total monstrous plan can be effected.

Wrapped for eternity: the story of the Egyptian mummy (Laurel-leaf library, ,, 1976)
Explores the mysteries of the mummification process, tomb robbing, x-raying of mummy bundles, and myths about mummies.

The girl who owned a city (Laurel-Leaf library, ,, 1995)
When a plague sweeps over the earth killing everyone except children under twelve, ten-year-old Lisa organizes a group to rebuild a new way of life.

Starring Sally J. Freedman as herself (Laurel-leaf library, ,, 2005)
While spending the winter of 1947-1948 in Miami Beach with her family, ten-year-old Sally makes up stories, casts herself in starring roles in movies, and encounters a sinister stranger.

Presenting S.E. Hinton (Twayne's United States authors, TUAS 528,, 1987)
Discusses the life and works of well-known author S.E. Hinton.